2018
DOI: 10.1016/j.dss.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Using LIWC to choose simulation approaches: A feasibility study

Abstract: Can language usage help determine which model approach is best suited to provide decision makers with desired insights? This research addresses that question through an investigation of Linguistic Inquiry and Word Count (LIWC), which calculates the presence of more than 80 language dimensions in text samples, and permits construction of custom dictionaries. This article demonstrates use of LIWC to ensure better problem/model fit within the context of selecting a decision support tool. We selected two simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Essays with low factor loadings tended to be personal stories (26). Initially labeled the categorical-dynamic index, this pole of the psychological dimension was later renamed analytic (27)(28)(29). Conversely, individuals scoring low on such measures of analytic thinking have been found to use higher rates of function word categories, such as pronouns, negations, auxiliary verbs, and so on-such linguistic features serve as signifiers of a more "intuitive" style of thinking (30,31).…”
mentioning
confidence: 99%
“…Essays with low factor loadings tended to be personal stories (26). Initially labeled the categorical-dynamic index, this pole of the psychological dimension was later renamed analytic (27)(28)(29). Conversely, individuals scoring low on such measures of analytic thinking have been found to use higher rates of function word categories, such as pronouns, negations, auxiliary verbs, and so on-such linguistic features serve as signifiers of a more "intuitive" style of thinking (30,31).…”
mentioning
confidence: 99%
“…We consider four main modelling methods in what follows: discrete event simulation, agent-based modelling, system dynamics and hybrid simulation. It is suggested that the choice of modelling method is made based on decision makers' requirements, type of problem and system complexity and its characteristics (Tako & Robinson, 2009Borshchev & Filippov, 2004;Brennan et al, 2006;Chahal & Eldabi, 2010;McHaney et al, 2018).…”
Section: Simulation Modelling Methodsmentioning
confidence: 99%
“…LIWC has been widely applied (e.g. McHaney et al , 2018; Tausczik and Pennebaker, 2010) and is considered an effective tool for measuring the psychological aspects of language (e.g. Iliev et al , 2015; Kahn et al , 2007).…”
Section: Methodsmentioning
confidence: 99%